Age-specific and sex-specific weight gain norms to monitor antiretroviral therapy in children in low-income and middle-income countries. (2nd January 2015) - Yotebieng, Marcel; Meyers, Tammy; Behets, Frieda; Davies, Mary-Ann; Keiser, Olivia; Ngonyani, Kapella Zacharia; Lyamuya, Rita E.; Kariminia, Azar; Hansudewechakul, Rawiwan; Leroy, Valeriane; Koumakpai, Sikiratou; Newman, Jamie; et al.
Abstract : Background: Viral load and CD4% are often not available in resource-limited settings for monitoring children's responses to antiretroviral therapy (ART). We aimed to construct normative curves for weight gain at 6, 12, 18, and 24 months following initiation of ART in children, and to assess the association between poor weight gain and subsequent responses to ART. Design: Analysis of data from HIV-infected children younger than 10 years old from African and Asian clinics participating in the International epidemiologic Databases to Evaluate AIDS. Methods: The generalized additive model for location, scale, and shape was used to construct normative percentile curves for weight gain at 6, 12, 18, and 24 months following ART initiation. Cox proportional models were used to assess the association between lower percentiles (< 50th) of weight gain distribution at the different time points and subsequent death, virological suppression, and virological failure. Results: Among 7173 children from five regions of the world, 45% were underweight at baseline. Weight gain below the 50th percentile at 6, 12, 18, and 24 months of ART was associated with increased risk of death, independent of baseline characteristics. Poor weight gain was not associated with increased hazards of virological suppression or virological failure. Conclusion: Monitoring weight gain on ART using age-specific and sex-specific normative curves specifically developed for HIV-infected children on ART is a simple, rapid, sustainable tool that can aid in the identification of children who are at increased risk of death in the first year of ART. Abstract : Supplemental Digital Content is available in the text